Perception of Risk on Interest in Using Online Loans as an Alternative Education Financing - Yudesti, Rahmi; Matoati, Rindang (Sharia Business Management UIN Raden Intan Lampung, 2024)
Education played an important role in improving the quality of human resources. However, the high cost was an obstacle for many people to continue to a higher level. According to the Central Statistics Agency (BPS), the cost of education rises 10%-15% every year, with the cost of higher education reaching IDR 14.47 million in 2020/2021. The increase in tuition fees at some universities also added to the burden on students. On the other hand, advances in financial technology offered financing solutions through online loans. However, this option often comes with various risks. The purpose of this study was to analyze the perception of risk on the interest in making online loans as an alternative education financing. This research was a quantitative study with a voluntary sampling technique and used the Structural Equation Modeling-Partial Least Square (SEMPLS) analysis method. The results showed that all aspects of risk perception consisting of financial risk, security risk, psychological risk, and performance risk had a negative and significant effect on interest in making online loans as an alternative to education financing.